Transition Towards Cancer Mortality Predominance over Cardiovascular Disease Mortality in Brazil, 2000–2019: A Population-Based Study - De Moraes-Ferrari, G (Elsevier Ltd, 2024)
Background: Cardiovascular disease (CVD) and cancer are the first and second leading causes of death in Brazil and worldwide. However, an ongoing epidemiological transition in which cancer surpasses CVD has been observed in many high and middle-income countries. In this study, we provided a nationwide analysis of the transition towards cancer mortality predominance over CVD mortality in Brazil. Methods: We leveraged data from 5570 municipalities using the Mortality Information System and classified the causes of death using ICD-10 codes. Age-standardized CVD and cancer mortality rates were calculated annually between 2000 and 2019. Mortality rate ratios (MRRs = CVD rates divided by cancer rates) described the predominance of cancer or CVD mortality across municipalities and states. Choropleth maps displayed state-specific MRRs and the transition in the predominant cause of death over time. Findings: From 2000 to 2019, CVD mortality rates declined in 25 out of 27 states, whereas cancer mortality increased in 15 states, indicating a shift towards cancer predominance. While in 2000 cancer mortality was lower than CVD in all states and only exceeded the latter in 7% of the municipalities, by 2019 the gap narrowed considerably, with 13% of municipalities displaying higher cancer mortality rates vs CVD mortality rates. Additionally, higher household income correlated with higher mortality from cancer vs CVD. Interpretation: An ongoing epidemiological transition in which cancer mortality surpasses CVD mortality is occurring in Brazil, particularly in municipalities with higher household incomes. Our findings may provide important information for policymakers and public health practitioners in Brazil. Funding: National Council for Scientific and Technological Development (CNPq). © 2024 The Author(s)